Supply Chain and Logistics Management in the Automotive Industry in Bekasi, Indonesia - Muhammad, Reza (Generasi Sains Indonesia, 2024)
This paper will look at how supply chain efficiency will influence profitability of firms operating in the automobile industry in Bekasi Indonesia. The survey to achieve this objective was conducted within 50 automotive firms using quantitative research method wherein structured questionnaires were delivered to measure the key variables of supply chain performance, i.e. inventory turnover, percentage of orders fulfilled, lead time and supplier quality. Paired samples t-tests, multiple regression, ANCOVA, and Pearson correlation were used to find the relationship between these variables and the profitability of a firm. The findings indicate that the turnover rate of finished goods inventory, higher order fulfillment rates, and preferable quality of suppliers bear positive correlation with enhanced profitability and long lead times have a demeriting impact on the financial performance. The results further indicate that the efficiency of supply chain has major impact on profitability, which remains stabile despite many other factors that can affect the results such as company size. These findings support the fact that integrated and effective supply chain practices are important in boosting functional and financial effectiveness in the manufacturing industry. The paper is ranked as a contribution to the literature, as it proves the validity of the application of the theory of supply chain management even to the emerging markets, and to offer practical solutions to the automotive companies, interested in improving their competitiveness with applying effective supply chain optimization. It also suggests utilizing modern technologies to enhance visibility of the supply chain, supply chain agility as well as taking decisions.